2007
DOI: 10.1007/s11816-007-0007-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of salt tolerance in transgenic rice expressing an Escherichia coli catalase gene, katE

Abstract: Rice (Oryza sativa) is sensitive to salt stresses and cannot survive under low salt conditions, such as 50 mM NaCl. In an attempt to improve salt tolerance of rice, we introduced katE, a catalase gene of Escherichia coli, into japonica rice cultivar, Nipponbare. The resultant transgenic rice plants constitutively expressing katE were able to grow for more than 14 days in the presence of 250 mM NaCl, and were able to form flower and produce seeds in the presence of 100 mM NaCl. Catalase activity in the transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 32 publications
1
28
0
1
Order By: Relevance
“…Sudhakar et al, (2001) have shown that CAT activity increases by more in salt tolerant mulberry cultivars $1 than salt susceptible cultivar ATP at higher concentration of NaCI. The Escherichia coli catalase encoded by the kate gene overexpressed under CaMV35S promoter in Japonica rice (Oryza sativa) conferred transgenic rice plants tolerance to the salt and catalase activity being about 1-5 to 2.5 times more than non-transgenic plants (Nagamiya et al, 2007). sion of antioxidant defence enzymes in transgenic plants (Lee et al, 2007).…”
Section: Antioxidants In Plantsmentioning
confidence: 99%
“…Sudhakar et al, (2001) have shown that CAT activity increases by more in salt tolerant mulberry cultivars $1 than salt susceptible cultivar ATP at higher concentration of NaCI. The Escherichia coli catalase encoded by the kate gene overexpressed under CaMV35S promoter in Japonica rice (Oryza sativa) conferred transgenic rice plants tolerance to the salt and catalase activity being about 1-5 to 2.5 times more than non-transgenic plants (Nagamiya et al, 2007). sion of antioxidant defence enzymes in transgenic plants (Lee et al, 2007).…”
Section: Antioxidants In Plantsmentioning
confidence: 99%
“…Hence, different attempts have been made to overexpress catalase genes in plants with the aim to increase plant stress resistance. For example, introduction of KatE from E. coli into tobacco and rice resulted in high tolerance to drought and salinity in the crops, respectively [22][23][24]. Transgenic Arabidopsis containing the broccoli catalase gene BoCAT showed heat tolerance by removing the H 2 O 2 accumulated due to high temperature [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, plant's capacity to effi ciently metabolize has been extensively reported to be signifi cantly improved by overexpressing a range of genes associated with ROS scavenging/detoxifying enzymes including aldehyde dehydrogenases (ALDHs) (Nakazono et al 2000 ), Mn-superoxide dismutase (Mn-SOD) (McKersie et al 1996 ;Gusta et al 2009 ;Waterer et al 2010 ), ascorbate peroxidases (APX) (Wang et al 2006 ), and catalase (CAT) (Nagamiya et al 2007 ). In transgenic rice plants, Zhao and Zhang ( 2006 ) constitutively co-expressed glutathione-S -transferase (GST) and CAT genes and achieved improved tolerance to salinity-caused oxidative stresses (Zhao and Zhang 2006 ).…”
Section: Detoxifying Reactive Oxygen Speciesmentioning
confidence: 99%